FREQUENT MONITORING OF WATER TEMPERATURE IN PEGAMETAN BAY, BALI: A PRELIMINARY ASSESSMENT TOWARDS MANAGEMENT OF MARINE AQUACULTURE DEVELOPMENT - I Nyoman Radiarta; Erlania Erlania; Ketut Sugama; Hirmawan Tirta Yudha; Masaaki Wada (Indonesian Aquaculture Journal, 2014)
Aquaculture currently share for nearly half of the world’s food fish consumption, and continue to be the fastest-growing animal food producing sector. The viability of aquaculture operation has greatly been affected by the characteristic of marine environment. Inventory and monitoring of marine environment are necessary and can be done through information technology implementation. Frequent monitoring of water temperature, for almost one year observation, at four aquaculture sites in Pegametan Bay and Research and Development Institute for Mariculture was investigated. Water temperature data were obtained by using logger and buoy systems. These data were contrasted against marine fish mortality. On the other hand, the suitability of species requirements with the thermal conditions was evaluated by comparing temperature range to the optimum and lethal temperature information available on marine fish species of aquaculture interest. This research could be beneficial for enhancing productivity of marine aquaculture operation in terms of possible impact of climate change. It was also possible to find the ideal temperature range for culturing fish species, taking into account the variability associated with large-scale phenomena.